Ways to identify factors contributing to the occurrence of road traffic accidents - Kairatolla K. Abishev; Almagul N. Baltabekova; Assylbek Zh. Kassenov; Ruslan B. Mukanov; Karlygash B. Assylova (Acta Polytechnica CTU Proceedings, 2024)
The article deals with the issues of determining the factors contributing to the occurrence of road accidents. On the basis of statistical studies, the main factors most fully reflecting the process of occurrence of road traffic accidents were identified. For this purpose, an expert-statistical method was used. Road safety assessment was carried out on the example of the roads of the city of Pavlodar. The results obtained allow, in the future, to build a mathematical model that characterizes the possibility of a traffic accident.